L’IMPACT ENVIRONNEMENTAL ET LA QUESTION DE LA SANTÉ MENTALE DANS UNE COMMUNAUTÉ FORESTIÈRE AU SUD DE LA CÔTE D’IVOIRE - Noël, Abe N’doumy (European Scientific Journal, ESJ, 2014)
This Communication responds to the requirement of the interface of ecology and religion which leads us into a multidisciplinary field where cross geography, theology and anthropology. It is a cultural community located in forest areas. This community is faced with a frantic pace of change and deformation of its ecological environment for economic reasons. An ecological crisis began Community sanctuary. Coincidence or cause and effect? It is given to find a kind of general psychopathology settle within the community in question. The emic approach to the phenomenon observed supports the thesis of spiritual decommissioning is to say the abandonment of the sanctuary by the community because of the ecological crisis. What appears indisputable is the passage of a type of “society therapeutic orientation” to a "Company pathogen." Deep unease settled. How contrasts restore normal mental state of this community? A solution is itself possible outside? How can the community rebuild itself springs? The importance of the issue is the extent of the ecological issue in the problem of modernization of African societies. This particular experience is only considered a pretext to draw the attention of policy makers and also to echo the cry of the heart of the environmental movement in the interest of the future of all humanity.